Mathematical Modelling in Management of Railways Timetable Based on Circulation Scheme and Rescheduling Approach - Singh, B.K.; Singh, Rajan; Tiwari, Nidhi; Prabhakar, Nidhi (Mathematics and Computer Science: Research Updates Vol. 2, 2025)
In each country, the railway system plays an important role in transporting goods and human beings. In India, for example; Railways are accountable for 30% of the transportation of the total number of goods. In this chapter, an integer linear programming model was discussed on the basis of the fixed departure or arrival of trains, in the case of the original timetable and corresponding circulation scheme. The main objective of this chapter is to optimize the circulation scheme in order to get more connections, especially without changing the direction of the trains.